Gambaran Pengetahuan dan Sikap Ibu Hamil Tentang Isi Buku Kesehatan Ibu dan Anak (Kia) - Setyadi, Deddy Yusuf Tri, Sulastri, S.Kp., M.Kes, Endang Zulaicha Susilaningsih, S.Kp., M.Kep (2016)
The use KIA book is primarily a family community empowerment strategies to maintain their health and get the mother and child health care quality. As the goal of the program guide KIA, the mother should also understand the finer points of the contents of the book so that the utilization KIA KIA book can be done optimally. This study aims to describe the knowledge and attitude of pregnant women about the content of books Maternal and Child Health (MCH). This study is a descriptive analysis. The study population is pregnant women who had routine checks in BPM Rima Village Gubug Cepogo District of Boyolali and a sample of 35 pregnant women with total sampling technique. Collecting data using questionnaires knowledge and attitudes, while data analysis using quantitative descriptive. The conclusion of the study (1) the level of knowledge of pregnant women about the contents of the book KIA in RM Rima Village Gubug District of Cepogo Boyolali majority is less (40%) and (2) the attitude of pregnant women about the contents of the book KIA in RM Rima Village Gubug District of Cepogo Boyolali most of it is enough (66%).